Responding to Risk: Regulation or Prohibition? New Zealand Media Reporting of Thoroughbred Jumps Racing 2016–2018 - Kylie A. Legg (Animals, 2019)
Jumps racing involves a higher risk of accident and fatality than flat racing. The wide accessibility of media, combined with alternate views regarding the place of animals in society, raises the question of the acceptability of the continuation of jumps racing. Racing data and media articles from Newztext and Google news search were collected for the 2016/2017 and 2017/2018 jumps racing seasons, during which the fatality rate was 5.8 per 1000 starters. Jumps racing articles comprised 3.4% of all race reporting, and the volume of discussion about jumps racing was minimal (2.9% of jumps race articles related to the continuation of jumps racing), short-lived and related to horse fatalities. Articles were categorised and analysed using rhetorical analysis to determine the main arguments. The inherent risk posed by jumps racing to the horse formed a basis for two argumentative positions. Proponents of jumps racing argued that risks were reasonable, with risk minimisation measures best determined by expertise and care from within the racing industry, labelling opponents as naïve extremists. Opponents of jumps racing used anthropomorphism of the horse to argue that any risk was unacceptable and jumps racing should be banned. Horses were attributed with rights, and from this perspective, the racing industry exploited horses for entertainment. These two different arguments were used to shape claims for and against the continuation of jumps racing, allowing both to be built upon a shared acceptance of inherent risk.